Critical success factors of micro entrepreneurs under the AIM and Asnaf's economic development programme / Farah Aida Ahmad Nadzri - Ahmad Nadzri, Farah Aida (2016)
The microfinance concept was introduced by Professor Muhammad Yunus in 1970s with the aspiration to improve the poor people live by providing them the accessibility to the financial services. Generally, the microfinance programs in Malaysia can be divided into two categories, repayable and non-repayable micro funds. As previous studies on repayable financing by Microfinance Institutions such as Amanah Ikhtiar Malaysia (AIM) suggested that in general, the programme has a positive socio-economic impact, empirical studies on the economic development programmes by Zakat Institutions that provide the non-repayable micro funds showed that the successful or effectiveness of this programme is questionable. Therefore, this thesis aims to study on the critical success factors of micro entrepreneurs under the AIM and Program Pembangunan Usahawan Asnaf Zakat Selangor (PPUAZ). Based on the previous literature, a conceptual framework is developed that the performance of micro entrepreneurs under the AIM and PPUAZ is causally related to four factors, namely financial management; human capital; social networking; and entrepreneurs' characteristics. In order to meet the objective of this study, the quantitative (surveys) and qualitative (interviews) approaches are used. The surveys were conducted first in order to explain the relationship between the four critical success factors and the performance of the micro-entrepreneurs. Later, the findings from the questionnaire were verified in the interview sessions with 17 randomly selected participants. Based on the surveys conducted, it was found that financial management and human capital have positive significant impact on the financial performance of the micro entrepreneurs, while financial management, human capital, and social networking have positive significant impact on the non-financial performance of the micro-entrepreneurs. Interestingly, it was also found that the AIM participants are financially performing better as compared to the asnafs PPUAZ, however, the asnafs PPUAZ score higher in term of the non-financial performance as compared to the AIM sahabats. However, based on the interviews and observation, this study found that to some extent, all the four factors suggested by the previous literatures do affect the overall performance of the micro entrepreneurs. Despite the SEM analysis suggesting that Person Entrepreneurship Fit does not affect the performance of the micro entrepreneurs, the observation however found that there were some differences between the attitudes of the successful micro entrepreneurs as compared to the others. Moreover, this study did also suggest a new model named "Islamic Microfinance Business Model" to further enhance the effectiveness of the current microfinance practice.